Co-Expression of the B-Cell Key Transcription Factors Blimp-1 and IRF4 Identifies Plasma Cells in the Pig - Villanueva-Hernández, Sonia; Adib Razavi, Mahsa; van Dongen, Katinka A.; Stadler, Maria; de Luca, Karelle; Beyersdorf, Niklas; Saalmüller, Armin; Gerner, Wilhelm; Mair, Kerstin H. (Frontiers in Immunology, 2022)
Antibody-secreting plasma cells (PCs) have remained largely uncharacterized for years in the field of porcine immunology. For an in-depth study of porcine PCs, we identified cross-reactive antibodies against three key transcription factors: PR domain zinc finger protein-1 (Blimp-1), interferon regulatory factor 4 (IRF4), and paired box 5 (Pax5). A distinct Blimp-1+IRF4+ cell population was found in cells isolated from blood, spleen, lymph nodes, bone marrow, and lung of healthy pigs. These cells showed a downregulation of Pax5 compared to other B cells. Within Blimp-1+IRF4+ B cells, IgM-, IgG-, and IgA-expressing cells were identified and immunoglobulin-class distribution was clearly different between the anatomical locations, with IgA+ PCs dominating in lung tissue and IgM+ PCs dominating in the spleen. Expression patterns of Ki-67, MHC-II, CD9, and CD28 were investigated in the different organs. A high expression of Ki-67 was observed in blood, suggesting a plasmablast stage. Blimp-1+IRF4+ cells showed an overall lower expression of MHC-II compared to regular B cells, confirming a progressive loss in B-cell differentiation toward the PC stage. CD28 showed slightly elevated expression levels in Blimp-1+IRF4+ cells in most organs, a phenotype that is also described for PCs in mice and humans. This was not seen for CD9. We further developed a FACS-sorting strategy for live porcine PCs for functional assays. CD3-CD16-CD172a– sorted cells with a CD49dhighFSC-Ahigh phenotype contained Blimp-1+IRF4+ cells and were capable of spontaneous IgG production, thus confirming PC identity. These results reveal fundamental phenotypes of porcine PCs and will facilitate the study of this specific B-cell subset in the future.